The Idea of Healthy Lifestyle and Its Transformation Into Health-Oriented Lifestyle in Contemporary Society - Olga Pakholok (SAGE Open, 2013)
The major subject matter of the proposed article is the gap between global value of health and its practical implementation in the form of actual daily practices. The article addresses the concept of health in contemporary society and claims healthy lifestyle ideology to be the essence of contemporary health culture. Thus, this ideology is discussed as a basic framework proposed by the modern discourse with respect to body practices management as it builds up its logic of practice. Meanwhile, health-oriented lifestyle is considered to be a practical logic derived out of it. The author shows that there are four types of interconnection between the logical practice and the practice of logic, whereas health-oriented lifestyle is one of them. The article aims to demonstrate that health-oriented lifestyle concept in its visionary ideal form is quite far from being a practical guide for daily human behavior. Human beings are not ready to fight all their affections although they know much and sometimes they feel they can do much. This means that the basic ground for an evident discord between the high value of health and its practical incorporation into daily activities of concrete individuals lies in the field of physicality matters and civilization’s disability to manage them.